Adaptation of MC3T3 cell line to Dulbecco's Modified Eagle's medium. (June 2020) - Bahraminasab, Marjan; Arab, Samaneh; Jahan, Ali
Highlights: Comparison of direct and sequential cell adaptation was done. Direct exposure to the new medium leaded to slow cell growth as the cells experienced stress and shock. Sequential adaptation processes were more efficient. Sequential adaptation 2 resulted in higher number of cells in fewer days. Mathematical models were provided and correctly predicted the number of cells by day. Abstract: Seeding cells directly into a new medium subjects the cells to stress due to certain differences in medium formulation. As a result, it seems necessary for cells to be adapted to a new medium, in order to save the properties of the cells and to achieve reliable results from the tests. The MC3T3 osteoblastic cell line is recommended to be cultured in Alpha Minimum Essential Medium (α-MEM). However, Dulbecco's Modified Eagle's medium (DMEM) is widely used for its culture. Therefore, in the present paper, two sequential methodologies were applied to adapt the MC3T3 cells to DMEM. In sequential adaptation 1, 10 vol.% DMEM was added to the original medium every day, while in sequential adaptation 2, the old medium was changed to a new medium having 20 vol.% higher DMEM content after each passage. Cells were monitored and compared to direct cell adaptation, while they were growing. The results showed that in the direct cell adaptation, increase in the number of cells was very slow. In contrast, the two sequential adaptation processes were more efficient where sequential adaptation 2 resulted in a higher number of cells in fewer days; 88 % greater than sequential adaptation 1 when it was believed that the cells were adapted. Furthermore, the statistical analysis was conducted by stepwise regression analysis and mathematical models were provided, which can predict the number of cells by day of culture.